The geography of tourism of Central and Eastern European countries - Widawski, Krzysztof; Wyrzykowski, Jerzy (Springer, 2017)
This book presents a comprehensive overview of the tourism market development in Central and Eastern European countries. It is divided into 13 chapters, including a chapter dedicated to Belarus, all richly illustrated with colorful maps and illustrations. The book presents the output of international conferences organized every two years by the Department of Regional Geography and Tourism of the University of Wroclaw which have served as inspiration for this book. Chapter 1 provides the characteristics of 20 post-communist countries of the region on the international tourism market and it sets the background and context for the following chapters. Chapters 2 to 13 present the condition of research on tourism, tourist attractions, tourist infrastructure, tourism movement, main types of tourism as well as tourist regionalization in 12 Central and Eastern European countries. All chapters have been updated with reference to the statistics. This book is a revised and updated version of "The Geography of Tourism of Central and Eastern Europe Countries" published by the Department of Regional Geography and Tourism of Wroclaw University in 2012. It has been developed by a group of specialists through their exchange of research experience in the scope of international tourism in Central and Eastern Europe.- Resumé vydavatel